Primary hyperoxaluria type I diagnosed after a kidney transplant presenting with subcutaneous calcification: a case report of sodium thiosulfate treatment - Wu, Min; Lu, Jing; Wang, Yu-Jia; Li, Yong-Qi; Wei, Qing; Gong, Yu-Xiang; Tang, Ri-Ning (Frontiers in Pharmacology, 2025)
Primary hyperoxaluria (PH) is a rare autosomal recessive disorder that results from the overproduction of endogenous oxalate. The diagnosis of PH is often delayed or missed owing to its rarity, variable clinical expression and other diagnostic challenges. In this study, we report a patient with a frameshift variant, c.823_824dup, in the alanine-glyoxylate aminotransferase (AGXT) gene of PH1 who presented with renal failure recurrence after kidney transplantation, arteriovenous fistula (AVF) occlusion and subcutaneous calcification in adulthood. Skin biopsy revealed heavy deposition of calcium oxalate crystals in subcutaneous tissue without vascular oxalosis. After 6 courses of sodium thiosulfate (STS) treatment, X-rays of the bilateral hands showed the disappearance of subcutaneous calcification on the extremity of the left-hand ring-finger. This case highlights the importance of broad diagnostic testing prior to transplantation in patients who present with end-stage renal disease with unclear etiology. In addition, STS may be useful for PH1 patients with subcutaneous calcium deposits.